Chicana Feminisms : A Critical Reader - Zavella, Patricia; Nájera-Ramírez, Olga; Klahn, Norma; Hurtado, Aída; Arredondo, Gabriela F. (Book collections on Project MUSE., 2003)
An anthology of original essays from Chicana feminists which explores the complexities of life experiences of the Chicanas, such as class, generation, sexual orientation, age, language use, etc.